COMPARISON OF AGE-RELATED CHARACTERISTICS OF CEPHALOMETRIC INDICATORS: FRONTAL CHORD (N–B) AND PARIETAL CHORD (B–L) IN ARTIFICIALLY DEFORMED AND NORMAL SKULLS - Abdullayev, A.S. (World of Medicine and Biology, 2025)
This study aimed to compare the age-related characteristics of two cephalometric indicators – frontal chord (n–b) and parietal chord (b–l) – in artificially deformed and normal human skulls. A total of 254 skulls (200 non-deformed and 54 with artificial cranial deformation) from the craniological collection of Azerbaijan Medical University were analyzed. Measurements of the n–b and b–l chords were performed using digital and sliding calipers. Across all age intervals, skulls with artificial deformation showed consistently higher average values for both cephalometric parameters: in the second adulthood group, the mean frontal chord in deformed skulls was 112.3 mm versus 108.6 mm in non-deformed skulls. Similarly, the mean parietal chord in deformed skulls was 110.1 mm compared to 108.2 mm in the non-deformed group. This trend was evident across all age categories, with particularly strong differences observed in the elderly group.
Keywords: cephalometry; cranial deformation; frontal chord; parietal chord; skull morphology; age-related changes; anthropometry; craniology